MENINGKATKAN LITERASI DIGITAL BAGI GURU DALAM MENGHADAPI PEMBELAJARAN DARING DI MASA COVID 19 - gilang maulana jamaludin; Nuruddin Araniri; syafa'atun nahriyah (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
In the 21st century in 2019, the whole world is in an uproar with the presence of a virus that spreads so quickly and easily to all levels of any country, the virus is now familiar to us, namely The Corona Virus Disease 2019 (COVID19). The Covid-19 pandemic has had a considerable impact, including in the world of education, especially in the learning process. The learning process during the COVID-19 pandemic is certainly different, learning that is usually face-to-face has now been turned into online learning. In this case, of course, teachers must understand a good level of digital literacy because the online learning process requires skills and mastery of technology. The purpose of this community service is to provide training to elementary school teachers as an effort to increase understanding of digital literacy in dealing with online learning during the covid 19 pandemic. The method used is training using lectures, demonstrations and Q&A. This community service provides benefits for elementary school teachers in developing digital literacy skills, especially in online learning during the COVID-19 pandemic.